A dictionary of entomology - Gordh, Gordon; Headrick, David (CABI, 2011)
This fully updated new edition of the Reference Reviews Top Ten Print Reference Source 2004 is a comprehensive, fully cross-referenced collection of terms, names and phrases used in entomology, incorporating an estimated 43,000 definitions. It is the only listing which covers insect anatomy, behaviour, biology, ecology, histology, molecular biology, morphology, pest management, taxonomy and systematics. The origin, etymology, part of speech and definition of each term and phrase are all provided, including the language, meaning or root of each term and constituent parts.The common names of insects, their scientific binomen and taxonomic classification are provided, with diagnoses of pest species in many cases. All insect order, suborder, superfamily, family and subfamily names are given, together with the diagnostic features of orders and families. With new and updated terms, particularly in molecular biology, phylogeny and spatial technology, this is an essential reference for researchers and students of entomology and related disciplines